COMPARATIVE CHARACTERISTIC OF NATIONAL AND INTERNATIONAL CORPORATE LAW - Umirzakhova Умирзахова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
Questions considered in given article are actual in civil-legal science and study basic moments maintenance in corporative law